(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
We have already shown how consumerism has established itself as a set of modern rituals (Vincenzo, 2014). With the beginning of the twentieth century, the consumer goods were at the center of the symbolic representations that have filled the anomic void of society, the emptiness of symbols and rituals. As time passed, however, advertising has saturated modern imagination. The resulting consumer’s alienation has led to a shift from the consumption of material goods to the entertainment industry, to the “free time” consumption. We want to show how the anomie-saturation-alienation cycle is one of the fundamental characteristics of the order of a ritual society. In a society like ours, based on consumerism, the cycle concerned the advertising communication in particular. This was reiterated in the digital world, with commercial use of big data coming from the web. Relations between rituals, theater and entertainment world receive special attention. This text is a concise presentation of a broader research project on the social rituals and the social history of advertising, realized in partnership with Fausto Lupetti.